Effects Of Cycle Peak Temperature Ratio On The Performance Of Combined Cycle Power Plant - Ibrahim, Thamir K.; M. M., Rahman (Universiti Malaysia Pahang, 2016)
Combined cycle power plant (CCPP) is currently the most promising technology to generate power at higher plant thermal efficiencies. The effects of the cycle peak temperature ratio on the improvement of the performance of the combined cycle power plant had been proposed. The MATLAB code was developed to utilize the performance of the CCPP. The results of this study showed that the overall thermal efficiency increased with the increase of cycle peak temperature ratio and decreased with the increase of air fuel ratio. Also, the increase of the cycle peak temperature ratio as well as the increase of the isentropic compressor efficiency led to the increase of the total power output. The thermal efficiencies for CCPP were higher compared to the gas turbine power plant